2020
DOI: 10.1021/acsbiomaterials.9b01857
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Titania Nanotubes Fabricated on Ti–Nb Alloys: Surface Topography, Structure, Physicomechanical Behavior, and a Cell Culture Assay

Abstract: In this study, hybrid composites based on β-alloy Ti−xNb and oxide nanotubes (NTs) have been successfully prepared. NTs of different sizes were grown on Ti−Nb substrates with different Nb contents (5, 25, and 50 wt %) via electrochemical anodization at 30 and 60 V. Scanning electron microscopy imaging revealed that vertically aligned nanotubular structures form on the surface of Ti−Nb alloy substrates and influence Nb content in alloys based on NT length. X-ray diffraction analysis confirmed the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 69 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…As a classic type of orthopedic implant, Ti6Al4V prostheses are widely used for the treatment of large bone defects. Although many other titanium alloys, such as Ti–Nb alloys [ 33 ], exhibit excellent mechanical properties and biocompatibility, Ti6Al4V remains indispensable for clinical applications and bone tissue engineering [ 34 ]. In recent years, porous Ti6Al4V scaffolds have attracted more attention due to their low overall modulus of elasticity, excellent mechanical properties, and good ingrowth of new bone [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a classic type of orthopedic implant, Ti6Al4V prostheses are widely used for the treatment of large bone defects. Although many other titanium alloys, such as Ti–Nb alloys [ 33 ], exhibit excellent mechanical properties and biocompatibility, Ti6Al4V remains indispensable for clinical applications and bone tissue engineering [ 34 ]. In recent years, porous Ti6Al4V scaffolds have attracted more attention due to their low overall modulus of elasticity, excellent mechanical properties, and good ingrowth of new bone [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ti alloys, Renjie et al [294] proposed that the compaction/reduction of the α-phase and/or increase in the amount of the β-phase was the most important factor in promoting the mechanical biocompatibility of the surface. Recently, Chernozem et al [296] reported the anodic deposition of TNTs on β-alloy Ti-xNb hybrid composites (x ¼ 5, 25 or 50) and it was observed that there was a significant increase in β-phase elements in the alloy leading to an increase in the surface's elastic modulus after anodisation. The surface load-deformation behaviour of TNTs on Ti-50Nb was reduced by approximately 17% when compared to TNTs structure on Ti-Nb composites with lower wt% Nb and by approximately 23% when compared to cp-T [296].…”
Section: Techniques To Enhance Mechanical Stability Of Anodic Tio 2 Layermentioning
confidence: 99%
“…Recently, Chernozem et al [296] reported the anodic deposition of TNTs on β-alloy Ti-xNb hybrid composites (x ¼ 5, 25 or 50) and it was observed that there was a significant increase in β-phase elements in the alloy leading to an increase in the surface's elastic modulus after anodisation. The surface load-deformation behaviour of TNTs on Ti-50Nb was reduced by approximately 17% when compared to TNTs structure on Ti-Nb composites with lower wt% Nb and by approximately 23% when compared to cp-T [296]. Regarding Young's modulus, the value obtained for the β-alloy Ti-xNb hybrid composites coated with TNTs was approximately the same as that of bone (ca.…”
Section: Techniques To Enhance Mechanical Stability Of Anodic Tio 2 Layermentioning
confidence: 99%
See 2 more Smart Citations